A Cross-Cultural Study on Behaviors When Death Is Approaching in East Asian Countries. Issue 39 (September 2015) - Cheng, Shao-Yi; Suh, Sang-Yeon; Morita, Tatsuya; Oyama, Yasuhiro; Chiu, Tai-Yuan; Koh, Su Jin; Kim, Hyun Sook; Hwang, Shinn-Jang; Yoshie, Taeko; Tsuneto, Satoru; Wang., Wen-Hung
<x xml:space="preserve">Abstract</x> Abstract The primary aim of this study was to explore common beliefs and practices when death is approaching in East-Asian countries. A cross-sectional survey was performed involving palliative care physicians in Japan, Korea, and Taiwan. Measurement outcomes were physician-perceived frequencies of the following when patient death was approaching: (1) reluctance to take part in end-of-life discussions, (2) role of family members, (3) home death, and (4) circumstances surrounding death. A total of 505, 211, and 207 responses were obtained from Japanese, Korea, and Taiwan physicians, respectively. While 50% of the Japanese physicians reported that they often or very often experienced families as being reluctant to discuss end-of-life issues, the corresponding figures were 59% in Korea and 70% in Taiwan. Two specific reasons to avoid end-of-life discussion, "bad things happen after you say them out loud" and "a bad life is better than a good death" were significantly more frequently observed in Taiwan. Prioritizing the oldest of the family in breaking bad news and having all family members present at the time of death were significantly more frequently observed in Korea and Taiwan. Half of Taiwanese physicians reported they often or very often experienced the patients/family wanted to go back home to die because the soul would not be able to return from the hospital. In all countries, more than 70% of the physicians reported certain family members were expected to care for the patient at home. At the time of death, while no Japanese physicians stated that they often experienced patients wanted a religious person to visit, the corresponding figure in Korean and Taiwan was about 40%. Uncovered expression of emotion was significantly frequently observed in Korean and Taiwan, and 42% of the Japanese physicians reported family members cleaned the dead body of the patient themselves. There seem to be significant intercountry differences in beliefs and practices when death is approaching in East Asian countries. Future studies on direct observations of patients and families are needed.